Advocates and Gatekeepers: Dialogue on the Multiple Roles of Cooperating Teachers and University Supervisors - Katherine Mason Cramer (The Advocate, 2020)
Using Valencia et al.’s 2009 article “Complex Interactions in Student Teaching: Lost Opportunities for Learning” as a starting point for dialogue, cooperating teachers (CTs), recent graduates, and current teaching candidates of an English Education Program participated in focus group discussions on the attributes of effective CTs and university supervisors. CTs expressed some anxiety regarding mentors’ roles as gatekeepers, as well as understanding regarding the necessity of this role. Additionally, CTs, candidates, and graduates viewed the CT’s role as one that is more hands-on early in the field experience with decreasing direct guidance as the candidate develops in her or his professional practice. Implications for practice include explicitly articulating advocate and gatekeeper roles to candidates at the start of each field experience, intentionally discussing candidates’ pedagogical content knowledge during post-observation conferences, bridging the perceived gap from theory to practice, directly addressing uncooperative CTs, and strategically sharing mentoring resources.
Keywords: mentoring; cooperating teacher; teaching candidate